Unusual coordination behavior by a hydroxypyridine/pyridone ligand: Synthesis and structure of [(2-bromo-4-hydroxypyridine)2(2-bromo-1(H)-4-pyridone)2copper(II)] perchlorate 2(2-bromo-4-hydroxypyridine) 2(2-bromo-1(H)-4-pyridone). Issue 19 (2nd November 2019) - Monroe, Jeffrey C.; Turnbull, Mark M.
Abstract: The synthesis and structure of [Cu(2-Br-4-HOpy)2 (2-Br-4-pyone)2 ](ClO4 )2 2(2-Br-4-HOpy) 2(2-Br-4-pyone) is reported [2-Br-4-HOpy = 2-bromo-4-hydroxypyridine; 2-Br-4-pyone = 2-bromo-(1H)4-pyridone]. The compound forms as a co-crystal in the triclinic P-1 space group with four-coordinate Cu(II) ions and perchlorate geganions interacting with both the hydroxypyridine and pyridone forms of the organic molecule through hydrogen and halogen bonding. The coordination complex exhibits the unusual coordination motif of having both the hydroxypyridine and pyridone tautomers of the ligand coordinated to the same metal ion. The isolation of the Cu complex by the organic groups suggests an absence of magnetic exchange within the sample which is confirmed by variable temperature magnetization measurements and EPR data. Abstract :